MANAJEMEN MUTU AKADEMIK SD NEGERI WONOYOSO - Purnomo, Heru; Murniati, Ngurah Ayu Nyoman; Miyono, Noor (Journal Prakarsa Paedagogia, 2022)
The academic quality achieved by SD Negeri Wonoyoso is very proud because of the well-organized management from planning, organizing, implementing to supervising. This study uses a qualitative approach. The research was conducted at SDN Wonoyoso. Data collection techniques were carried out through interviews, observation and documentation studies. Data analysis procedure with data reduction, data presentation and data verification. While the research subjects were principals, heads of foundations, teachers, committees and school supervisors. The results showed that: 1) the implementation of academic quality management at SD Negeri Wonoyoso was carried out in a structured manner starting from planning, organizing, implementing and supervising by involving the active roles of principals, teachers, committees, heads of foundations, supervisors and parents of students. . 2) in the functions and responsibilities of academic quality in schools placing personal according to their respective competencies. 3) the obstacles experienced include the urgent need to improve coordination of each field, high loyalty, completeness of administration and infrastructure. Academic quality management is needed in changing educational organizations. This is important for organizational innovation and adaptation to management practices. Academic quality management will be realistic when placing the quality of educational services and the quality of graduates in accordance with the needs of the community